(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
Over the past three decades, the internationalization not higher education has become a priority in the development to higher education in Uzbekistan. The importance of internationalization is reflected in the fact that it has become a dominant strategy for the development of higher education. It has also become a key factor in the development of the national economy and the mechanisms for the development of cultural diversity and the development of the national education system. This article examines the process of internationalization of higher education in Uzbekistan in the context of ongoing reforms in higher education. In particular, it discusses the role of internationalization of higher education in Uzbekistan. The main purpose of the article is to provide a brief history of the event, its current state, as well as the basics of internationalization of higher education in Uzbekistan.